Effect of an herb root extract, herbal dentifrice and synthetic dentifrice on human salivary amylase - Gaurav Sapra; Yogesh Kumar Vyas; Rahul Agarwal; Ashish Aggarwal; K T Chandrashekar; Kanika Sharma (Wolters Kluwer Medknow Publications, 2013)
Background: Salivary amylase is an enzyme, which plays a vital role in formation of dental plaque. It has the ability to bind on the bacterial surfaces and to hydrolyze starch, giving rise to products that are transformed into acids leading to dental caries. Suppression of salivary amylase activity can lead to decrease in risk of dental caries and plaque associated periodontal diseases. The aim of this study was to evaluate the effect of an herb, Spilanthes calva (in form of a test dentifrice) on human salivary amylase activity and to compare it with other dentifrices. Materials and Methods: A total of 80 subjects of age 18-35 years were randomly selected and divided equally into 4 groups. Group 1 subjects were assigned to use Test Dentifrice (with S. calva root extract), while Group 2, Group 3, and Group 4 subjects were assigned to use Herbal Dentifrice (Arodent™ ), Synthetic Dentifrice (Colgate ® ), and Control Dentifrice respectively. Salivary amylase activity was determined by Bernfeld method in each group, before and after using the given dentifrices. Results: Maximum inhibition of salivary amylase activity was found in the group using test dentifrice as compared to others. Conclusion: The present study indicates that, the root extract of S. calva possess significant inhibitory activity for salivary amylase. Use of S. calva root extract will provide a wider protection against different pathogenic oral microflora. Use of this extract singly or in combination is strongly recommended in the dentifrice formulations.